Ambliopía refractiva paciente femenino de 9 años de edad. - Moreno Ortiz, Lesly Solange (2022)
Amblyopia is a pathology characterized by the most common loss of visual acuity in childhood with no detectable cause; it occurs when vision in one or both eyes does not develop correctly during childhood. Its main symptoms are: poor vision in one or both eyes, poor depth perception, headaches, difficulty in calculating distances, poor school performance, etc. In refractive amblyopia the brain when receiving two different visual stimuli chooses the best image and suppresses the vision of the most affected eye, generating a poor visual development, but recoverable with proper treatment at an appropriate age, one of the consequences of amblyopia is anisometropia, which is that each eye has a different refractive error. Any impairment of vision affects the quality of life of the sufferer. The present clinical case corresponds to a 9-year-old female patient who comes to the optometrist's office with blurred distance vision, headache, constant blinking, eye fatigue when performing activities such as reading or using digital devices. The general objective of this clinical analysis is to identify the origin of the decrease in visual acuity in the left eye of the 9-year-old patient. Through the application of examinations and optometric tests among which we can mention Visual Acuity, Biomicroscopy, Kappa Angle, Ocular Motility, Cover Test, Bruckner Reflex, Hirschberg Test, Titmus Test, Ishihara Test and Ophthalmoscopy, when analyzing the results, anisometropic myopic refractive amblyopia was diagnosed. The patient's treatment was based on optical correction, in addition to visual therapy with an eye patch complemented with the use of Tetris video games, as well as optometric controls twice a month to verify the progress of the visual treatment.